Clinical effectiveness of a patient decision aid to improve decision quality and glycaemic control in people with diabetes making treatment choices: a cluster randomised controlled trial (PANDAs) in general practice. Issue 6 (5th November 2012) - Mathers, Nigel; Ng, Chirk Jenn; Campbell, Michael Joseph; Colwell, Brigitte; Brown, Ian; Bradley, Alastair
Abstract : Objective: To determine the effectiveness of a patient decision aid (PDA) to improve decision quality and glycaemic control in people with diabetes making treatment choices using a cluster randomised controlled trial (RCT). Design: A cluster RCT. Setting: 49 general practices in UK randomised into intervention (n=25) and control (n=24). Participants: General practices Inclusion criteria: >4 medical partners; list size >7000; and a diabetes register with >1% of practice population. 191 practices assessed for eligibility, and 49 practices randomised and completed the study. Patients People with type 2 diabetes mellitus (T2DM) taking at least two oral glucose-lowering drugs with maximum tolerated dose with a glycosolated haemoglobin (HbA1c) greater than 7.4% (IFCC HbA1c >57 mmol/mol) or advised in the preceeding 6 months to add or consider changing to insulin therapy. Exclusion criteria: currently using insulin therapy; difficulty reading or understanding English; difficulty in understanding the purpose of the study; visual or cognitive impairment or mentally ill. A total of 182 assessed for eligibility, 175 randomised to 95 intervention and 80 controls, and 167 completion and analysis. Intervention: Brief training of clinicians and use of PDA with patients in single consultation. Primary outcomes: Decision quality (Decisional Conflict Scores, knowledge, realistic expectations and autonomy) and glycaemic control (glycosolated haemoglobin, HbA1c). Secondary outcomes: Knowledge and realistic expectations of the risks and benefits of insulin therapy and diabetic complications. Results: Intervention group: lower total Decisional Conflict Scores (17.4 vs 25.2, p<0.001); better knowledge (51.6% vs 28.8%, p<0.001); realistic expectations (risk of 'hypo', 'weight gain', 'complications'; 81.0% vs 5.2%, 70.5% vs 5.3%, 26.3% vs 5.0% respectively, p<0.001); and were more autonomous in decision-making (64.1% vs 42.9%, p=0.012). No significant difference in the glycaemic control between the two groups. Conclusions: Use of the PANDAs decision aid reduces decisional conflict, improves knowledge, promotes realistic expectations and autonomy in people with diabetes making treatment choices in general practice. ISRCTN Trials Register Number: 14842077.